Analysis of three-phase Inverter with switching angle variations - Marsha Kirana, Fabiola; Asnil (Department of Electrical Engineering Universitas Negeri Padang, 2025)
A three-phase inverter is a power conversion device that converts direct current (DC) to three-phase alternating current (AC). Inverter performance is significantly influenced by the switching angle control method used. This study analyzed three-phase inverters with varying switching angles of 30°, 45°, 60°, 90°, 120°, 135°, 150°, and 180°. The objective of this study was to determine the effect of varying the switching angle on the output waveform produced by the three-phase inverter. Testing was conducted by observing the gate driver output signal and the phase-to-phase and phase-neutral voltage waveforms using an oscilloscope. The results showed that changes in the switching angle affected the voltage pulse width and the symmetry of the output waveform. The higher the level, the closer it became to a sinusoidal shape. This test used two loads: the resistive load produced a relatively stable waveform, while the incandescent lamp load experienced distortion due to the inductive nature of the filament. The conclusion of this study is that selecting the right switching angle can improve the power quality and efficiency of the inverter performance according to application needs.